Inequality, good governance and endemic corruption - Gil S. Epstein; Ira N. Gang (Rutgers University, Department of Economics, 2017)
Can a society suffering contests between rich and poor achieve good governance in the face of endemic corruption? We examine a stylized poor state with weak institutions in which a "culture of evasion" damages state authority. Many evade tax payments, limiting the state's economic development capability. In the face of extensive corruption, it is challenging for the state to establish and implement policies reflecting good governance; for example, a government that is accountable and transparent, efficient and effective, and follows the rule of law. The rich and poor possess different views on what is the appropriate level of enforcing proper payments of taxes due. The government needs to design an effective tax administration policy that minimizes corruption and is sensitive to the present and future needs of society. To do this it must understand what drives such widespread corruption.
Keywords: O12; O15; O16; D82; G38; 330; corruption; tax administration; governance; rent-seeking